STUDI POLA KONSUMSI AIR DOMESTIK MASYARAKAT MULTIETNIS DI KELURAHAN KARANG INDAH DISTRIK MERAUKE - Widiastuti, Maria M. D.; Mangera, Paulus (KRITIS, 2020)
The purposes of this study are: (1) To estimate the real number of people who live- in Kelurahan Karang Indah; (2) To analyze the pattern of domestic water consumption of Kelurahan Karang Indah community; (3) To analyze the ethnic characteristics of the domestic water consumption patterns; (4) To analyze the adaptation and mitigation community of the clean water. The results showed that the real number of people who live in Kelurahan Karang Indah was two times higher than the statistic data. The water consumed for domestic activities was 51.6 liters/day/capita which is higher than Indonesian National Standar (46 liters/day/capita). There are no significant differences in the patterns of domestic consumption between dry season and rainy season. Awyu people were known for using more water than other tribes especially for bathing, drinking and washing, while for cooking Marind people use more water than other tribes. There is no specific adaptation- in clean water consumptions. The people adaptation for water consumption are indicated by their habit of drinking less water than required, queuing up at night to get clean water and using poor water quality for bathing or washing.